Antioxidant and antiproliferative properties of 3-deoxyanthocyanidins. (1st February 2016) - Sousa, André; Araújo, Paula; Azevedo, Joana; Cruz, Luís; Fernandes, Iva; Mateus, Nuno; de Freitas, Victor
Highlights: Overall, the strategies followed to synthesize the different deoxyanthocyanidins were well succeeded. The six deoxyanthocyanidins studied presented antioxidant capabilities. Deoxyanthocyanidins have antiproliferative effects, being active against caco-2 cell line. Abstract: The study of the antioxidant properties of six deoxyanthocyanidins (deoxypeonidin, deoxymalvidin, luteolinidin, apigeninidin, guaiacylcatechinpyrylium and syringylcatechinpyrylium) and an anthocyanin (cyanidin-3-glucoside) was carried out. The aim was to evaluate the relationship between the structure and the antioxidant properties of individual deoxyanthocyanidins, compared to a common anthocyanin derivative, cyanidin-3-glucoside. The ability of these compounds to inhibit lipid peroxidation in a liposome membrane system was examined by monitoring oxygen consumption and the antiradical and reducing capacities were determined using the DPPH and FRAP assay, respectively. The results showed that all the compounds tested presented antioxidant properties. Cyanidin-3-glucoside presented higher antiradical and reducing activities in the DPPH and FRAP assay, although in the liposome model, the guaiacylcatechinpyrylium was more effective inhibiting lipid peroxyl radicals. Additionally, the anti-proliferative effects of deoxyanthocyanidins, have been evaluated against two cancer cell lines from stomach (AGS, MKN-28) and one colon cancer cell (Caco-2), and compared with the effect of the respective anthocyanins. Considering the antiproliferative activity, all compounds were active against Caco-2 cell line, being the ones with glucose moiety and oaklin Scp the most active. Deoxyanthocyanidins, and in particular, guaiacylcatechinpyrylium may be regarded as potential food colorants.